DIRECTIONS OF CONSOLIDATION OF THE UKRAINIAN NATION IN THE POST-COLONIAL EPOCH - Drobotenko, Mykola (Київський національний університет імені Тараса Шевченка, 2019)
Some issues of consolidation of the Ukrainian nation are considered. The peculiarity of postcolonial discourse is the study of new types of cultural and social identities, issues of self-conceptualization, and the legitimization of local narratives as national ones. It is known that the phenomenon of collective identity has attracted the attention of many researchers and is actively debated in various social and humanitarian discourses. Foreign science studies this phenomenon mainly according to sociocultural anthropology, sociology and psychology from various theoretical and methodological positions (Z. Freud, E. Erickson, K. Jung, B. Anderson, M. Barrett, S. Bauman, F. Bart, E. Gellner, R. Jenkins, H. Kon, B. Connor, B. Lukman, D. Matteson, A. Melutchchi, J. G. Mead, M. Mead, K. Moscovichi, E. Smith, G. Tejfel, J. Turner, J. Habermas, S. Huntington, etc.). In Russian and Ukrainian science, identity is studied within the framework of philosophy, political science, sociology, cultural studies, and psychology. The author extrapolated the Ericksonian term "identity" to the concept of "national identity". The components of this concept are analyzed, the interconnection of the components is searched and directions of consolidation of Ukrainians are offered.The emphasis is made on the fact that the level of their morality, synthesized from the various feelings inherited from their predecessors during many centuries of existence of the Ukrainian people on the lands of modern Ukraine, should be considered a special feature of Ukrainian national identity. Historical facts of the formation of the modern Ukrainian people prove the immutability of his desire for freedom, justice, dedication to their ideals, on which the modern society is based and around which consolidation of the people of Ukraine is possible. It is noted that, speaking of the uniqueness of the Ukrainian nation, one should mention its ideological principles, which allowed Ukrainians to defend their interests and protect the values on which national identity is based. It is emphasized that understanding the essence and ways of any consolidation is based on the natural physical laws of the existence of matter, of the world - this should be taken into account in the process of achieving the goal.

Розглянуто окремі питання консолідації української нації. Особливістю постколоніального дискурсу є вивчення нових типів культурної та соціальної ідентичностей, питань самоконцептуалізації, легітимації локальних наративів у якості національних. Відомо, що феномен колективної ідентичності давно привертає увагу багатьох дослідників і активно обговорюється в різних соціальних та гуманітарних дискурсах. Зарубіжна наука вивчає це явище переважно у відповідності з соціокультурною антропологією, соціологією та психологією з різних теоретичних та методологічних положень (З. Фройд, Е. Еріксон, К. Юнг, Б. Андерсон, М. Барретт, З. Бауман, Ф. Барт, Е. Гелнер, Р. Дженкінс, Г. Кон, В. Коннор, Б. Лукман, Д. Маттесон, А. Мелуччі, Дж. Г. Мід, М. Мід, К. Московичі, Е. Сміт, Г. Теджфел, Дж. Тернер, Дж. Габермас,С. Гантінгтон та ін.). У російській та українській науці ідентичність вивчається в рамках філософії, політології, соціології, культурології, психології. Автором екстрапольовано Еріксонівський термін «ідентичність» на поняття «національна ідентичність». Проаналізовано складові частини цього поняття, проведено пошук взаємозв’язку складових частин і запропоновано напрямки консолідації українців. Акцентовано на тому, що особливою рисою національної ідентичності українців слід вважати рівень їх моральності, що синтезований із різних почуттів, успадкованих від попередників протягом багатьох віків існування українського народу на землях сучасної України. Історичні факти становлення сучасного українського народу доводять незмінність його потягу до свободи, справедливості, відданості своїм ідеалам, на яких ґрунтується сучасне суспільство і навколо яких є можливою консолідація народу України. Зазначено, що, говорячи про унікальність української нації, слід згадати про її світоглядні засади, які дозволяли українцям відстоювати свої інтереси і захищати цінності, які лежать в основі національної ідентичності. Підкреслено, що розуміння сутності і шляхів будь-якої консолідації базується на природних фізичних законах існування матерії, світу, – це має бути враховано у процесі досягнення поставленої мети.
НАПРЯМКИ КОНСОЛІДАЦІЇ УКРАЇНСТВА ПОСТКОЛОНІАЛЬНОЇ ДОБИ
Keywords: consolidation; people; national identity; history of the people; консолідація; народ; національна ідентичність; історія народу